Immune Microenvironment Change and Involvement of Circular RNAs in TIL Cells of Recurrent Nasopharyngeal Carcinoma - Wang, Yumin; Peng, Zhouying; Wang, Yaxuan; Yang, Yi; Fan, Ruohao; Gao, Kelei; Zhang, Hua; Xie, Zhihai; Jiang, Weihong (Frontiers in Cell and Developmental Biology, 2021)
Nasopharyngeal carcinoma is a malignant tumor that is highly prevalent in southern China and the Southeast Asian belt. Recent studies have shown that the T cells play important regulatory roles in tumorigenesis and progression. We test TIL cell of recurrent nasopharyngeal carcinoma and primary nasopharyngeal carcinoma cell. We found that T cell change in recurrent nasopharyngeal carcinoma and primary nasopharyngeal carcinoma cell. Based on GEO database, we selected differently expressed circRNAs in nasopharyngeal carcinoma tissues. qRTPCR show that some circRNAs also highly expressed in TIL cells. In conclusion, immune microenvironment changed in recurrent nasopharyngeal carcinoma. There is involvement of circular RNAs in this progress, with should be researched further.